Borehole seismic monitoring of CO2 storage within a saline aquifer at Ketzin, Germany - Götz, J.; Giese, R.; Lüth, S.; Schmidt-Hattenberger, C.; Juhlin, Christopher; Cosma, C. (European Association of Geoscientists and Engineers, EAGE, 2011)
The borehole seismic monitoring in the in situ laboratory for saline aquifer CO2 storage (Ketzin, Germany) comprises crosswell tomography, offset-VSP, walkaway-VSP, and single level 3D-VSP. Timelapse measurements of the crosshole tomography indicated a decreased P-wave velocity of the rock units affected by CO2 injection, the walkaway-VSP observed increased reflectivity from the sandstone layers of the formation. The offset-VSP and 3D-VSP provide structural geometry and characterization in the vicinity of the site. A particular challenge will be the time-lapse processing of surface-to-borehole data.